Pola Pembelajaran Pendidikan Agama Islam Dalam Pendidikan Inqlusi Bagi Anak Yang Berkebutuhan Khusus (ABK) di SDIT Al Aufa Kota Bengkulu - Hengki Satrisno; Heny Friantary (Institut Agama Islam Negeri Bengkulu, 2019)
Education makes the needs of every human being, as an effort to maximize all the potential of the creator in order to become our human being. No exception for individuals who physically and psychologically have deficiencies and weaknesses called Children with Special Needs (ABK). To optimize the potential of these individuals, an appropriate learning pattern is needed, especially in the learning process of Islamic Religious Education. Al Aufa SDIT is an educational institution that provides Inclusive education services for ABK. Implement learning at SDIT Al Aufa using teacher and media learning patterns. Where this learning activity begins with compiling learning objectives, determining teaching material, establishing learning methods and media and evaluation instruments arranged simply. While learning activities in the classroom encountered several obstacles, namely the characteristics of ABK who were hyperactive, had difficulty communicating/ socializing and were slow in responding to the stimulus provided.